Polarization in Parliamentary Speech - Jon H. Fiva; Oda Nedregård; Henning Øien (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We study political polarization in a parliamentary setting dominated by strong parties. In addition to examining polarization along the left-right dimension, we consider political divergence between legislators belonging to the same political bloc. Are politicians' background characteristics unimportant when parties have powerful tools to discipline their rank-and-file? We investigate this question using legislative speech from the Norwegian Parliament and recently developed techniques for measuring group differences in high-dimensional choices. Across the background characteristics we consider — gender, age, urbanicity, and class background — we document substantial differences in speech, even when comparing legislators from the same party bloc and policy committee. Our results illuminate how individual legislators shape policymaking in party-centered environments.
Keywords: D72; 330; political polarization; text analysis; penalized logistic regression